Hungarian Scholar of Czechoslovak Law in the USA. The Life and Works of Miklós Ujlaki - Péter Nagy (Journal on European History of Law)
The study aims to present the life and carrier of Miklós Ujlaki, who was one of the students of the well-known Hungarian law professor, Károly Szladits (1871–1956). At the beginning of his academic career, Ujlaki researched the bibliography of the Hungarian private law. He researched the development of the private law in the former Hungarian territories for several years, which came under the control of neighbouring countries because of the Treaty of Trianon. He published his conclusions in several books. When the Communist dictatorship began to take hold, Ujlaki started a new life in New York. Miklós Ujlaki continued his research in the USA, mainly on legal bibliography and comparative law. In the first half of the 1950 s, his activities were based on academic research and teaching, and he became renowned in the fields of private international law and comparative law. He left academia in the mid-1950s and turned to practical work as a lawyer.